Stress in policing : research and practice - Burke, Ronald (Policing, 2007)
This e-book seeks to help with understanding the antecedents and consequences of police stress given the important functions policing serves in any community, leaving moot the question of whether policing places officers under more, the same or less stress than members of other professions.